2021
DOI: 10.31237/osf.io/ske5q
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sentence first, arguments after: Mechanisms of morphosyntax acquisition

Abstract: Natural languages contain complex grammatical patterns. For example, in German, finite verbs occur second in main clauses while non-finite verbs occur last, as in 'dein Bruder möchte in den Zoo gehen' (“Your brother wants to go to the zoo”). Children easily acquire this type of morphosyntactic contingency (Poeppel & Wexler, 1993; Deprez & Pierce, 1994). There is extensive debate in the literature over the nature of children’s linguistic representations, but there are considerably fewer mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 99 publications
(186 reference statements)
0
1
0
Order By: Relevance
“…Consequently, participants' behaviour in ex-periments provides an important source of evidence from which to draw conclusions about the link between learning and natural language structure. Previous studies have suggested that it is possible to learn V2 in an artificial language (Getz 2018, Rebuschat & Williams 2012, Tagarelli, Ruiz, Vega & Rebuschat 2016, Ruiz, Tagarelli & Rebuschat 2018. In our study, participants learn a novel miniature artificial language involving English lexical items which conform to a (non-English-like) V2 grammar.…”
Section: Artificial Language Learning Experimentsmentioning
confidence: 82%
“…Consequently, participants' behaviour in ex-periments provides an important source of evidence from which to draw conclusions about the link between learning and natural language structure. Previous studies have suggested that it is possible to learn V2 in an artificial language (Getz 2018, Rebuschat & Williams 2012, Tagarelli, Ruiz, Vega & Rebuschat 2016, Ruiz, Tagarelli & Rebuschat 2018. In our study, participants learn a novel miniature artificial language involving English lexical items which conform to a (non-English-like) V2 grammar.…”
Section: Artificial Language Learning Experimentsmentioning
confidence: 82%